Reflections on Unexpected Outcomes: Learning From Student Collaboration in an Online Discussion Forum - Clouder, Lynn; Deepwell, Frances (Proceedings of the International Conference on Networked Learning, 2004)
This paper reports the findings of the initial phase of an action research project involving the introduction of WebCT online discussion forums to facilitate reflection in undergraduate physiotherapy students. Students spend an introductory fifteen weeks away from University during which they gain hands on experience of professional practice in the workplace. This being a period of rapid development that is potentially stressful and challenging (Yuen, 1990; Mitchell & Kampfe, 1993; Clouder, 2001) the notion of providing an online collaborative space to develop reflective capabilities appeared sound. Findings suggest that certain assumptions were naïve. However, unforeseen benefits to such collaboration are discussed together with further ideas for encouraging critical reflection through online discussion.